2020
DOI: 10.3389/fpsyg.2020.00230
|View full text |Cite
|
Sign up to set email alerts
|

Social Networking Sites and Youth Transition: The Use of Facebook and Personal Well-Being of Social Work Young Graduates

Abstract: Research on youth transitions, and the well-being of young people, has to take into consideration the digital context in which they are immersed. Digital interaction of young people increase year by year, social networking sites play a key role in their personal and professional relationships, and a very high percentage of jobs require digital skills. According to Eurostat (2019), participating on social networking sites (one of the most common online activities in the EU-28), is growing every year [more than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 68 publications
1
19
0
2
Order By: Relevance
“…This information is relevant in the research of López-Fitzsimmons and Nagra [5], who indicated that Google is easier to use and more straightforward than library databases. However, this study confirmed the findings of Castillo de Mesa, Gómez-Jacinto, López Peláez, and Erro-Garcés [21], who found that Google and social media are also used by undergraduate students for educational purposes.…”
Section: Googlizationsupporting
confidence: 90%
See 1 more Smart Citation
“…This information is relevant in the research of López-Fitzsimmons and Nagra [5], who indicated that Google is easier to use and more straightforward than library databases. However, this study confirmed the findings of Castillo de Mesa, Gómez-Jacinto, López Peláez, and Erro-Garcés [21], who found that Google and social media are also used by undergraduate students for educational purposes.…”
Section: Googlizationsupporting
confidence: 90%
“…Other studies have found that Google and academic databases [20] are the students' preference during information search; the participants indicated that they have different perspectives about information resources. However, Castillo de Mesa, Gómez-Jacinto, López Peláez, and Erro-Garcés [21] indicated that social media is used by university students not only for engaging with friends and family but also for searching information related to their study.…”
Section: Brainstormingmentioning
confidence: 99%
“…This paper studies the role of ICT in young people's lives and its impact on social workers. By studying both collectives in parallel, the paper contributes to the previous literature on e-social work, young people, and technology (Castillo De Mesa et al, 2020;López Peláez et al, 2018;López-Peláez & Marcuello-Servós, 2018b). To this end, data from the International Digital Economy and Society Index 2019 and Eurostat were used for the analysis.…”
Section: E-social Work: a Meeting Ground For Young People And Social mentioning
confidence: 91%
“…In fact, although various studies have highlighted the positive effect of digital skills on young people's physical and psychological well-being and self-esteem, it has also been shown that technology does not solve all problems in and of itself, and that the acquisition of digital skills does not necessarily imply greater tolerance to diversity. 1 In dialogue with the monograph already published on young people in Social Work Education 2 in January 2020, this monograph addresses the invisibility of young people in different spheres of welfare states. As it shows, public policies are not as effective as they should be and do not adequately respond to young people's needs in relation to employability, social benefits, and other resources they require such as accessibility to digital training tools or even attractive leisure alternatives.…”
Section: Young People and Social Work Part IImentioning
confidence: 99%